How Does Local TV News Change Viewers' Attitudes? The Case of Sinclair Broadcasting. (2nd January 2022) - Levendusky, Matthew S.
ABSTRACT: How does local television news shape viewers' national political attitudes? The answer is unclear, because local news typically focuses on local, not national, stories, and is politically neutral. But the rise of Sinclair Broadcasting, now the nation's second-largest owner of local TV stations, upends that assumption. News on Sinclair-owned stations focuses more on national topics, and presents them with a right-wing slant. Given this, we might expect it to shift its viewers' attitudes in a pro-Republican direction. Using data on Sinclair's acquisition of local TV stations between 2008 and 2018, I show that living in an area with a Sinclair-owned TV station lowers viewers' approval of President Obama during his tenure in office, and makes viewers less likely to vote for the Democratic nominee for president. This has important implications for our understanding of the effects of local TV news, as well as for media trust, as I discuss in the conclusion.